REGULASI DAN SWA-REGULASI INDONESIA DALAM PENYELENGGARAAN MEDIA TERKAIT PERAN MNC GROUP TERHADAP PARTAI PERINDO - Al Azis, Muhammad Rachdian (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
In political contestation, the perpetrators are plural in taking various ways so that their political goals can be practically achieved. One of them is the use of mass media as a mouthpiece in increasing self-electability and political vehicles. Media has a role as the fourth pillar of the state after the Executive, Legislative, and Judicial powers. Because of its vital role, the media and the people behind it are required to be able to convey honest and useful information to the wider community. The existence of media owners who are involved and involved in the world of practical politics makes a preliminary indication of the increasing interest of a particular group. Indonesia, which upholds the rule of law, has established regulations and self-regulation for cases like this. Meanwhile, in the regulation and self-regulation of the media, it has been stipulated that the media must be neutral and not take sides with any party and not benefit the interests of individuals or groups. The government has the right and obligation to take action against the products produced by the media if a violation is found. Because the channels used by the media, especially public frequencies, do not belong to the media, but must be used for the greatest prosperity of the people.